Neurons Export Extracellular Vesicles Enriched in Cysteine String Protein and Misfolded Protein Cargo - Jingti Deng (Nature Portfolio, 2017)
Abstract The fidelity of synaptic transmission depends on the integrity of the protein machinery at the synapse. Unfolded synaptic proteins undergo refolding or degradation in order to maintain synaptic proteostasis and preserve synaptic function, and buildup of unfolded/toxic proteins leads to neuronal dysfunction. Many molecular chaperones contribute to proteostasis, but one in particular, cysteine string protein (CSPα), is critical for proteostasis at the synapse. In this study we report that exported vesicles from neurons contain CSPα. Extracellular vesicles (EV’s) have been implicated in a wide range of functions. However, the functional significance of neural EV’s remains to be established. Here we demonstrate that co-expression of CSPα with the disease-associated proteins, polyglutamine expanded protein 72Q huntingtinex°n1 or superoxide dismutase-1 (SOD-1G93A) leads to the cellular export of both 72Q huntingtinex°n1 and SOD-1G93A via EV’s. In contrast, the inactive CSPαHPD-AAA mutant does not facilitate elimination of misfolded proteins. Furthermore, CSPα-mediated export of 72Q huntingtinex°n1 is reduced by the polyphenol, resveratrol. Our results indicate that by assisting local lysosome/proteasome processes, CSPα-mediated removal of toxic proteins via EVs plays a central role in synaptic proteostasis and CSPα thus represents a potential therapeutic target for neurodegenerative diseases.